Control of aeration time in the aniline degrading-bioreactor with the analysis of metagenomic: Aniline degradation and nitrogen metabolism. (January 2022) - Peng, Haojin; Zhang, Yunjie; Zhang, Qian; Zhang, Wenli; Li, Meng; Feng, Jiapeng; Su, Junhao; He, Jing; Zhong, Min
Graphical abstract: Highlights: Aeration time affected system performance, sludge property and functional microflora. The aeration time of 5 h was the premise to ensure the degradation of aniline. The balance point for both nitrification and denitrification was 6 h aeration time. Excess aeration hindered sludge settling, boosted EPS secretion and reduced biomass. Functional flora enhanced the expression of key genes by acquiring more resources. Abstract: The strategy of adjusting aeration time (5 h/6 h/7 h) was applied to the sequential batch reactors to optimize the treatment of aniline wastewater (600 mg/L) conveniently and economically. Three reactors degraded aniline effectively. The nitrogen removal ability of system with 6 h aeration time was better, performing the similar denitrification property as 5 h and nitrification performance as 7 h. Meanwhile, longer aeration time potentially damaged the sludge structure. The metagenomic analysis explained the micro-mechanism for the better performance of the system with 6 h aeration time. Appropriate aeration time was conducive to the enrichment of synergistic microflora, including aniline degrading-bacteria, heterotrophic nitrifiers and denitrifiers. Then, the tilt of environmental resources to these floras in the system was beneficial to the maximum value utilization of living substrates. Accordingly, these bacteria were more closely related to genes, resulting in higher expression of functional genes in the system.